Investment Credit as a Source of Investment Financing - Rygielska, Sylwia; Wolska, Ewa (Journal of Finance and Financial Law, 2015)
The inspiration to write this article was the need for gaining information concerning investment credit, more often used as a source of investment financing. This subject is generally ignored in the literature or not described precisely enough. Therefore, the aim of this article is to raise the issue of financing investment credit in companies dating the economic crisis in Poland by the end of 2014 and to show the changes that have occurred during this period. Moreover, it examines the purpose and use of credit as well as involvement in comparison to other credits, that is, how much it was and is important in companies. We should concentrate on the period of crisis, as on the one hand the bad situation on the market forced banks to tighten lending procedures and reduce the money supply but on the other hand, traders to stay in business needed credit to finance core business. Thus, as demonstrated by the collected data, the most outstanding borrowings appeared on current account. As soon as the economic situation had improved the credit became more accessible for businesses. Currently, business needs changed slightly as instead of financing its core business they want to expand. Therefore the number of contracted investment credits increases.